Central Venous Pressure as a Predictor of Acute Kidney Injury in Cardiac Surgery: A Systematic Review of Observational Studies - Panagiota Griva; Vasiliki Griva; Dimitra Samara; Christina Talliou; Konstantina Panagouli; Loizos Roungeris (Diagnostics)
Background/Objectives: Acute kidney injury (AKI) is a syndrome characterized by impaired kidney function, which is associated with reduced survival and increased morbidity. Central venous pressure (CVP) is a widely used hemodynamic parameter for assessing the volume status of patients and evaluating their response to fluid resuscitation. This systematic review aims to analyze various prospective and retrospective observational and controlled trials to determine the association between CVP and the risk of developing AKI in patients undergoing cardiac surgery. Additionally, it examines whether elevated CVP serves as an accurate predictor of AKI in this patient population. Methods: A systematic review was conducted following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines, using PubMed as the primary database. The search focused on studies published after 2014 that included adult patients undergoing cardiac surgery with reported measurements of CVP and kidney function assessment. Studies conducted on animals, pediatric populations, those published before 2014, or in languages other than English were excluded from the review. Results: Through the analysis of 21 studies, a clear association between higher CVP and increased AKI risk emerged. The most critical CVP thresholds identified were 10 mmHg, 12 mmHg, 14 mmHg, and 20 mmHg, with risk increasing progressively beyond these values. CVP ≥ 10 mmHg was the most commonly reported cutoff for elevated AKI risk, showing 1.42 to 4.53 times increased odds. CVP ≥ 12 mmHg further amplified the risk, while CVP ≥ 14 mmHg was consistently associated with severe AKI and the need for RRT. The highest threshold (CVP ≥ 20 mmHg) showed the greatest risk escalation, linked to fluid overload, right heart failure, and mortality. Studies also suggest an optimal CVP range of 6–8 mmHg to minimize AKI incidence. Conclusions: Elevated CVP is an independent risk factor for the development of AKI in patients undergoing cardiac surgery. These findings suggest that CVP monitoring can play a significant role in predicting AKI and guiding perioperative management strategies.